Polyphenol-Rich Aronia melanocarpa Juice Consumption Affects LINE-1 DNA Methylation in Peripheral Blood Leukocytes in Dyslipidemic Women - Stojković, Ljiljana; Zec, Manja; Zivkovic, Maja; Bundalo, Maja; Bošković, Maja; Glibetić, Marija; Stankovic, Aleksandra (Frontiers in Nutrition, 2021)
Cardiovascular disease (CVD) is associated with alterations in DNA methylation and polyunsaturated fatty acid (PUFA) profile, both modulated by dietary polyphenols. The present parallel, placebo-controlled study (part of the original clinical study registered as NCT02800967 at www.clinicaltrials.gov) aimed to determine impact of 4-week daily consumption of polyphenol-rich Aronia melanocarpa juice treatment on Long Interspersed Nucleotide Element-1 (LINE-1) methylation in peripheral blood leukocytes and on plasma PUFAs, in subjects (n = 54, age of 40.2 ± 6.7 years) at moderate CVD risk including an increased body mass index, central obesity, high normal blood pressure and/or dyslipidemia. The goal was also to examine whether factors known to affect DNA methylation (folate intake levels, MTHFR C677T gene variant, anthropometric and metabolic parameters) modulated the LINE-1 methylation levels upon consumption of polyphenol-rich aronia juice. Experimental analysis of LINE-1 methylation was done by MethyLight method. MTHFR C677T genotypes were determined by polymerase chain reaction-restriction fragment length polymorphism method, and folate intake was assessed by processing the data from food frequency questionnaire. PUFAs were measured by gas-liquid chromatography and serum lipid profile was determined by using Roche Diagnostics kits. The statistical analyses were performed using Statistica software package. In the comparison after vs before the treatment period, in dyslipidemic women (n = 22) we observed significant decreases in LINE-1 methylation levels (97.54 ± 1.50% vs 98.39 ± 0.86%, respectively; P = 0.01) and arachidonic acid/eicosapentaenoic acid ratio (29.17 ± 15.21 vs 38.42 (25.96–89.58), respectively; P = 0.02). The change (after vs before treatment) in LINE-1 methylation correlated directly with MTHFR 677T allele presence, average daily folate intake and the change in serum low-density lipoprotein cholesterol, while inversely with the change in serum triacylglycerols (R = 0.72, R2 = 0.52, adjusted R2 = 0.36, P = 0.03). The current results imply potential cardioprotective effects of habitual polyphenol-rich aronia juice consumption achieved through the modifications of DNA methylation pattern and PUFAs in subjects at CVD risk, which should be further confirmed. Hence, the precision nutrition-driven modulations of both DNA methylation and PUFA profile may become targets for new approaches in the prevention of CVD.